Evidence for conifer sucrose transporters' functioning in the light-dependent adjustment of sugar allocation. (19th November 2021) - Han, Xiaoyu; Gao, Chen; Liang, Buyou; Cui, Jingxuan; Xu, Qiyu; Schulz, Alexander; Liesche, Johannes
Abstract: Sucrose is the central unit of carbon and energy in plants. Active intercellular transport of sucrose is mediated by sucrose transporters (SUTs), genes for which have been found in the genomes of all land plants. However, they have only been assigned functions in angiosperm species. Here, we cloned two types of SUTs from two gymnosperms, the conifers Cedrus deodara (Roxb. G. Don) and Pinus massoniana Lambert, and analyzed their sucrose transport activities. Uptake of the fluorescent sucrose-analog esculin into tobacco epidermis cells expressing the conifer SUT confirmed their transport ability. To determine their function in planta, we investigated their mRNA abundance in relation to photosynthesis and sugar levels in leaves, inner bark, wood and roots. Combined with measurements of protein abundance and immunolocalization of C. deodara SUTs, our results suggest a role for CdSUT1G and CdSUT2 in supporting phloem transport under varying environmental conditions. The implications of these findings regarding conifer physiology and SUT evolution are discussed.